A Conceptual Model of Hybrid Monitoring Rehabilitation Progress of Stroke Patients: A Case Study of a Public Tertiary Hospital in Malaysia - Ismail W.; Zamin N.; Hanafi M.H.; Mohamad A.H. (Institute of Electrical and Electronics Engineers Inc., 2024)
Indexed by WOS/SCOPUS